Perlindungan Hukum dan Dukungan bagi Korban Kekerasan dalam Rumah Tangga dalam Perspektif Viktimologi - Asya, Alisya Nur (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Legal protection for victims of Domestic Violence (DV) is an important issue within the criminal justice system in Indonesia. Although various regulations have been established through Law No. 23 of 2004 on the Elimination of Domestic Violence, significant challenges remain in providing optimal protection for victims, particularly from a victimological perspective. This study aims to examine the legal protection and support provided to DV victims, with a focus on a victimology-oriented understanding that prioritizes the interests of the victim. The research utilizes a library research method with a normative legal approach to analyze the legal protection for victims of domestic violence (DV). Data is collected through literature review from various secondary sources, such as regulations, legal documents, academic journals, and scholarly literature. This research analyzes relevant legal norms, including Law No. 23 of 2004, Islamic criminal law, positive Indonesian criminal law, and victimology perspectives. The collected data is analyzed descriptively through a normative approach to provide an understanding of the effectiveness of regulations in providing legal protection for DV victims. This analysis aims to provide in-depth insights into legal protection for DV victims in the context of both national and international law. The analysis concludes that legal protection for DV victims in Indonesia can be seen from three perspectives: positive Indonesian law, Islamic criminal law, and victimology. Law No. 23 of 2004 provides a strong legal basis, although challenges regarding victim awareness still persist. Islamic criminal law regulates sanctions for perpetrators and victims' rights, such as compensation (diyat). The victimology perspective emphasizes the importance of victim protection, including the right to compensation. Overall, legal protection should include penalties for perpetrators and recovery and justice for victims.